Identification of galangin as a therapeutic candidate for primary biliary cholangitis via systematic druggable genome-wide Mendelian randomization analysis and experimental validation - Ren, Weirui; Zhang, Chuang; Wang, Hanyan; Song, Hongzhao; Zhu, Xuejuan; Zhang, Zhijun; Zhao, Suxian; Wang, Junmin (Frontiers in Pharmacology, 2025)
BackgroundPrimary biliary cholangitis (PBC) is an immune-mediated cholestatic liver disease with currently limited therapeutic options. This study aimed to identify novel therapeutic targets for PBC via systematic druggable genome-wide Mendelian randomization (MR) analysis, predict candidate drugs, and experimentally validate the candidates.MethodsThe study integrated druggable genome data, cis-expression quantitative trait loci (cis-eQTL) in blood and liver tissues, and summary data from PBC genome-wide association studies (GWAS). Two-sample MR analysis and colocalization analysis were used to screen genes significantly associated with PBC, followed by phenome-wide association study (PheWAS), functional enrichment analysis, protein-protein interaction (PPI) network construction, drug prediction, and molecular docking. Finally, the therapeutic potential of the candidate drug galangin (GAL) was validated using an α-naphthylisothiocyanate (ANIT)-induced PBC mouse model.ResultsA total of 15 druggable genes significantly associated with PBC were identified, primarily enriched in biological processes regulating immune homeostasis, inflammatory signaling, and apoptosis, among others. Subsequent bioinformatic drug prediction and molecular docking identified GAL as a promising drug candidate, showing strong binding affinity to the target ADORA2A. Animal experiments showed that GAL reduced portal tract inflammation and bile duct hyperplasia in liver tissues, while reducing serum levels of liver enzymes (ALT, AST, ALP, etc.) and hepatic expression of inflammatory cytokines (IL-1β, IL-6, TNF-α).ConclusionBy integrating systematic druggable genome-wide MR analysis with experimental validation, this study identified 15 druggable genes associated with PBC. More importantly, it identified GAL as a therapeutic candidate for PBC, with its effects potentially mediated by the ADORA2A target. These findings provide novel therapeutic targets and drugs for PBC. Future research will focus on validating the functions of these druggable genes and elucidating the mechanistic pathway of the galangin-ADORA2A interaction, laying a more solid and comprehensive theoretical and practical foundation for PBC treatment.